2012
DOI: 10.7314/apjcp.2012.13.4.1709
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Cancer Registration in Indonesia

Abstract: Cancer is a major public health problem in Indonesia, becoming the 7th largest cause of death based on a national survey in 2007, accounting for 5.7 of all mortality. A cancer registry was started in 1970, but it was partial and was stopped mainly because no government body was responsible. Realizing the above situation, the Indonesian government established the Sub Directorate of Cancer Control within the Ministry of Health, with responsibility for developing a national cancer control program, including a can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 0 publications
0
60
0
5
Order By: Relevance
“…Almost similar overview regarding CaP is available in the recent literature from all over the world i.e. from China (Na et al, 2012;Xie et al, 2012), Indonesia (Wahidin et al, 2012), Nepal (Belbase et al, 2013), India (Takiar and Kumar, 2014) and Pakistan (Ahmad et al, 2009;Jamal et al, 2014).…”
Section: Introductionmentioning
confidence: 84%
“…Almost similar overview regarding CaP is available in the recent literature from all over the world i.e. from China (Na et al, 2012;Xie et al, 2012), Indonesia (Wahidin et al, 2012), Nepal (Belbase et al, 2013), India (Takiar and Kumar, 2014) and Pakistan (Ahmad et al, 2009;Jamal et al, 2014).…”
Section: Introductionmentioning
confidence: 84%
“…A study from Cambodia in 2012 reported that top five most common cancers were cervix, liver, lung, breast and stomach cancers (Eav et al, 2012). A study from Indonesia reported leading cancers were breast (ASR 18.6/100,000), cervix (9.25/100,000), lung (8.21/100,000), colorectal (7.28/100,000) and liver cancers (5.42/100,000) (Wahidin et al, 2012). Our study also shows that cancers affecting the breast and female reproductive/gynecological system were very common.…”
Section: Discussionmentioning
confidence: 99%
“…Even though, the expatriate population accounts for a small proportion of a population in most countries, it is important to be aware of the spectrum of disorders, including cancers, for future health planning and to understanding cancer characteristics in the global setting. International (IARC, 2012;Moore et al, 2012;) and country level (National Cancer Registry Singapore 2008National Cancer Registry Malaysia 2007) including hospital or regional level data have shown increasing and changing spectrum of cancers in the South-East Asia regions (Othman et al, 2008;Laudico et al, 2010;Wirasorn et al, 2010;Wahidin et al, 2012;Teo and Soo, 2013;Vuong et al, 2014). Studies on immigrant populations have shown the cancer patterns initially resemble the countries of origin, but with time with adoption of the new lifestyle, the pattern starts to change resembling the countries of residence (Ali et al, 2012;Maringe et al, 2012;Giddings et al, 2013;Menon et al, 2013).…”
Section: Cancers Among South-east Asian Nationals In Brunei Darussalammentioning
confidence: 99%
“…Indonesia: Data from the population-based cancer registry in Jakarta Province showed the leading cancers among females in 2005-2007 to be breast cancer, cervical cancer, ovarian cancer, colorectal cancer and among males are bronchus and lung cancer, colorectal cancer, liver cancer, pharyngeal cancer, and prostate cancer. The leading childhood cancers are leukaemia and retinoblastoma (Wahidin et al, 2012).…”
Section: South-east Asiamentioning
confidence: 99%